Taxonomic changes and description of two new species for the Phyllodactylus lanei complex (Gekkota: Phyllodactylidae) in Mexico - Ramírez-Reyes, Tonatiuh; Flores-Villela, Oscar (Zootaxa, 2018)
An integrative taxonomy approach was implemented based on analysis of genetic, phylogenetic, morphological and ecological data to identify the cryptic diversity within the Phyllodactylus lanei complex. At least six species can be identified, of which four are currently considered subspecies: Phyllodactylus lanei, Phyllodactylus rupinus, Phyllodactylus isabelae, Phyllodactylus lupitae and two corresponding to undescribed taxa, which are identified and described in this contribution. These differ from other Mexican geckos in several characters: genetic distance (DNAmt), position in molecular phylogeny (concatened data DNAmt+DNAnu), species tree, morphological characters such as snout-vent length, longitudinal scales, tubercles from head to tail, interorbital scales, scales across venter, third labial–snout scales and rows of tubercles across dorsum; there are also differences in their bioclimatic profiles (temperature and precipitation) and geographical distribution. The most recent studies on taxonomy and evolution of Mexican geckos (Phyllodactylus) show that the diversity of this group of reptiles is currently underestimated, suggesting that more research and conservation efforts are should be addressed at these lizards.